2005
DOI: 10.1590/s0103-50532005000700025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-substituted 6-trifluoromethyl-1,3-oxazinanes

Abstract: Este trabalho apresenta a síntese de duas novas séries de 6-trifluormetil-1,3-oxazinanas N-substituídas e 6-trifluormetil-1,3-oxazinan-2-onas N-substituídas, a partir da ciclização de 4-ilamino-1,1,1-trifluor-butan-2-óis com formaldeído e trifosgênio, respectivamente. Os 4-ilamino-1,1,1-trifluor-butan-2-óis foram obtidos através da reação de redução dos precursores 4-ilamino-1,1,1-trifluor-but-3-en-2-onas, utilizando hidrogênio e 10% Pd/C, com bons rendimentos.This work reports the synthesis of two new series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The Betti reaction, a Mannich-type aminoalkylation, offers a convenient route for preparing 1-(aminosubstituted methyl)-2-naphthols 2 under mild (rt) conditions. Access to these Mannich-type phenolic bases make the aminoalkylation reaction of naphthol derivatives a subject of current chemical interest [5][6][7]. Subsequent reaction of the aminobenzylnaphthtols with an equivalent amount of a substituted aldehyde in absolute MeOH at ambient temperature gave 1,3-naphthoxazines 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Betti reaction, a Mannich-type aminoalkylation, offers a convenient route for preparing 1-(aminosubstituted methyl)-2-naphthols 2 under mild (rt) conditions. Access to these Mannich-type phenolic bases make the aminoalkylation reaction of naphthol derivatives a subject of current chemical interest [5][6][7]. Subsequent reaction of the aminobenzylnaphthtols with an equivalent amount of a substituted aldehyde in absolute MeOH at ambient temperature gave 1,3-naphthoxazines 3.…”
Section: Resultsmentioning
confidence: 99%
“…Investigation of the 1,3-oxazine heterocycles has shown that they possess varied biological properties such as analgesic, anticonvulsant, antitubercular, antibacterial and anticancer activity [1][2][3][4]. Particular attention has been paid to these compounds since the discovery of the non-nucleoside reverse transcriptase inhibitor trifluoromethyl-1,3-oxazine-2-one, which shows high activity against a variety of HIV-1 mutant strains [5]. In addition, naphthoxazine derivatives have exhibited therapeutic potential for the treatment of Parkinson's disease [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…1,3-Oxazine derivatives have shown many biological properties such as analgesic, anticonvulsant, antitubular, antibacterial, antifungal, and anticancer activity [49][50][51][52][53][54][55][56]. Also, in the last decades, these compounds have been used in the treatment of AIDS and Parkinson's disease [57,58].…”
Section: Introductionmentioning
confidence: 99%
“…18 Unfortunately, in general, the processes to synthesize trihalomethyl substituted β-enamino ketones suffers from limitations, such as long reaction times, multi-step reactions and tedious work-up. 19,20 Thus, because of the applicability of β-enamino trihalomethyl ketones as a promising building blocks for the synthesis heterocycles, 21,22 a simple, general and high yielding onepot approach for the synthesis of this enaminones is highly desirable. In particular, it has been shown that syntheses which are carried out in solvent-free conditions are often rapid, regio-or chemoselective, occur in high yields and have environmental and economic advantages.…”
Section: Introductionmentioning
confidence: 99%